Flexural characteristics of novel carbon methylmethacrylate composites - Bhudolia, Somen Kumar (2021)
Reactive thermoplastic matrices are widely used for polymer composites manufacturing owing to their ease of processing using cost-effective liquid injection processes. The novel methyl methacrylate (MMA) Elium ® resin is a liquid thermoplastic resin, first of its kind which is curable at room temperature. It has attracted wide interest as a competitive solution to epoxy-based composites for structural applications. In this work, the flexural performances of novel non-crimp carbon fabric (NCCF) Elium ® composite laminates are evaluated. The baseline comparison is done with conventionally used composites with epoxy resin. The stress-strain curve, the fracture failure mechanisms and the effect of the annealing stage have been discussed.